Entangled White Identities: Christian and American Dimensions - Kang, Piljoo P. (Race and social problems, 2025)
Guided by an intersectional framework, this qualitative study examines how White emerging adults in the U.S. South construct racial identity at the crossroads of Christian faith, American nationalism, and regional culture. Semi-structured interviews were conducted with 36 self-identified White undergraduates at a Christian liberal arts college in the rural South. Using a Grounded Theory approach enriched with Consensual Qualitative Research procedures, transcripts were coded line by line, codes were refined through constant comparison, emerging themes were identified, and the analysis was audited for credibility. Three intertwined identity patterns emerged: (1) Whiteness as Christian, anchored in evangelical norms of morality, discipline, and community life; (2) Whiteness as Christian and American, in which religious discourse fused with civic nationalism to frame freedom and individual rights as distinctly White qualities; and (3) Whiteness as American and Southern, where regional customs and cultural pride implicitly encoded racial belonging. Participants seldom discussed Whiteness in isolation; instead, they experienced race as inseparable from their religious faith and national identity. This connection provided a sense of coherence and meaning but also generated ambivalence whenever issues of privilege or systemic inequality were raised. These findings extend scholarship on White identity by demonstrating how religion, patriotism, and regional heritage mutually reinforce racial self-understanding among young adults in predominantly White contexts. Implications are offered for higher education, counseling practice, and policy initiatives seeking to cultivate reflective racial consciousness and resilience among White young adults.